Analysis of selenium species using cathodic stripping voltammetry - Mohamed, Rugayah (Penerbit UTM Press, 2006)

(untitled)
Differential pulse cathodic stripping voltammetry of an inorganic selenium (selenite, Se(IV)) and organic selenium (dimethyl diselenide, DMDSe) was investigated using hanging mercury drop electrode (HMDE). The reduction peaks of selenite and dimethyl diselenide were obtained at –472 mV and –304 mV vs Ag/AgCl electrode respectively in acidic media. Various voltammetric parameters such as supporting electrolyte, accumulation potential and accumulation time were studied to establish the optimum condition for the determination of selenite and dimethyl diselenide. The detection limit of selenite and dimethyl diselenide was 8.175 × 10–9 M and 9.487 × 10–8 M respectively when an accumulation potential of 100 mV was applied for 90 seconds. Simultaneous determination of selenite and dimethyl diselenide was also carried out. The effect of selenite on the determination of dimethyl diselenide and vice versa was studied. The influence of metal ions such as lead, copper, cadmium and zinc on the reduction signals for selenite and dimethyl diselenide was also investigated.